Use of mobile phone for improvement in maternal health: a randomized control trial - Bangal, Vidyadhar B.; K. Borawake, Sai; P. Gavhane, Satyajit; H. Aher, Kunal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The rapid escalation of cellular network coverage and expansion of mobile phone usage has opened up a new way of deploying health services. The mobile app with message facilities help in imparting health education regarding nutrition, iron and folic acid prophylaxis, tetanus toxoid immunization, danger symptoms and signs during pregnancy etc. Present study aimed to improve maternal health and pregnancy outcome by optimum utilization of antenatal, natal and postnatal care services, with the use of mobile phone as a medium of communication between health care provider and community in rural area. Methods: The prospective randomized control study, with two hundred pregnant women each, coming for antenatal visit and having personal mobile phone facility, were randomly allocated to control and intervention group. Control group women received routine antenatal care and advice as per hospital protocol. In addition to routine care and advice, intervention group received mobile phone calls, as reminders about next visit and text messages (SMS) on important aspects of antenatal care at regular intervals. The primary outcome indicators of the study were percentage of pregnant women coming for at least four antenatal visits, percentage of institutional delivery and postnatal check-ups. Results: Women in the intervention group had significantly higher number of antenatal visits, consumption of iron tablets, tetanus toxoid immunization, institutional deliveries and postnatal check-ups as compared to the control group. Conclusions: In the present study, the mobile phone intervention, significantly increased the percentage of women receiving the recommended four antenatal visits and showed a trend towards more women receiving preventive health services. Study gathered good evidence that m-Health tools present an opportunity to influence behaviour change and ensure that women access prevention services, including antenatal, natal and postnatal care. Mobile technology, specifically SMS can be successfully used to extend health information services to pregnant women.